Quality of the water from the springs of the Paraíso settlement - Agrizzi, Daniela Vantil (2018)
The objective of this study was to evaluate the influence of land use in the surrounding of the springs on some of the parameters of water quality in eight springs located in the Paraíso settlement in the city of Alegre, Espírito Santo, Brazil. The springs evaluated were: one in the Atlantic forest remnant; six fenced ones and in different stages of forest recovery; and one without a fence and with free livestock access. Three samples of water were collected in each spring in 2011 and 2012, and 17 parameters were analyzed. The determined values were compared to the normative standards for water quality and linearly correlated through the correlation coefficient. Water from the springs showed to be consumable, if previously treated, and the more protected the springs, the better the water quality values.